1997
DOI: 10.1161/01.cir.95.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Small, Dense Low-Density Lipoprotein Particles as a Predictor of the Risk of Ischemic Heart Disease in Men

Abstract: These results represent the first prospective evidence suggesting that the presence of small, dense LDL particles may be associated with an increased risk of subsequently developing IHD in men. Results also suggest that the risk attributed to small LDL particles may be partly independent of the concomitant variation in plasma lipoprotein-lipid concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
547
4
21

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 998 publications
(594 citation statements)
references
References 36 publications
17
547
4
21
Order By: Relevance
“…The predominance of small dense LDL (sdLDL) was reported to be particularly atherogenic. This observation has been confirmed in prospective studies (Gardner et al, 1996;Stampfer et al, 1996;Lamarche et al, 1997). Several mechanisms have been proposed to explain this association: their low affinity to the LDL receptor, low resistance to oxidative stress, prolonged plasma half-life, high binding affinity to surface components in the vessel wall and efficient penetration into the intima (Chait et al, 1993;Chapman et al, 1998;Brewer, 1999).…”
Section: Introductionmentioning
confidence: 79%
“…The predominance of small dense LDL (sdLDL) was reported to be particularly atherogenic. This observation has been confirmed in prospective studies (Gardner et al, 1996;Stampfer et al, 1996;Lamarche et al, 1997). Several mechanisms have been proposed to explain this association: their low affinity to the LDL receptor, low resistance to oxidative stress, prolonged plasma half-life, high binding affinity to surface components in the vessel wall and efficient penetration into the intima (Chait et al, 1993;Chapman et al, 1998;Brewer, 1999).…”
Section: Introductionmentioning
confidence: 79%
“…But many studies have shown that factors other than total cholesterol and LDL-C must be considered when evaluating coronary artery disease (CAD) risks [12]. Recent studies have shown that the size of LDL particle is more important as compared to LDL-C concentration in atherogenesis [13,14]. In routine clinical practice estimation of LDL particle size is not applicable due to complicated methodology [15].…”
Section: Discussionmentioning
confidence: 99%
“…A several set of observations witnesses that the reduced LDL size is linked to the increased risk of CHD [116,117,118,119]. Both LDL size and the number of particles seems to increase synergistically the risk of CHD [120,121].…”
Section: Why Is Small Dense Ldl Highly Atherogenic?mentioning
confidence: 99%